Trifluridine/Tipiracil and Regorafenib in Patients with Metastatic Colorectal Cancer: A Retrospective Study at a Tertiary Oncology Center. (1st October 2021) - Patel, Anuj K.; Abhyankar, Ritika; Brais, Lauren K.; Duh, Mei Sheng; Barghout, Victoria E.; Huynh, Lynn; Yenikomshian, Mihran A.; Ng, Kimmie; Fuchs, Charles S.
Abstract : Background: Trifluridine/tipiracil (FTD/TPI) and regorafenib prolong survival for patients with refractory metastatic colorectal cancer (mCRC); limited comparative effectiveness data exist. Materials and Methods: A retrospective, longitudinal cohort study of patients with mCRC who initiated FTD/TPI or regorafenib (index therapy) between 2012 and 2017 at a U.S. tertiary oncology center, Dana-Farber Cancer Institute, was conducted. Using best tumor response assessments, real-world overall response rates (rwORR) and disease control rates (rwDCR) were described and analyzed using logistic regression. Survival rate was examined for each month after index therapy using Kaplan-Meier. Overall survival (OS) was assessed using Cox proportional hazards models. Subgroup analyses among patients with index therapy as second- or third-line were performed. Results: One hundred twenty-six and 95 patients were treated with FTD/TPI or regorafenib as index therapy, respectively. Patients treated with FTD/TPI versus regorafenib had a better response (rwORR 52.5% vs. 34.2%; adjusted odds ratio [OR] = 2.6; all p value <.05; rwDCR 64.2% vs. 46.1%; adjusted OR = 2.5; all p value <.05). Similar findings were observed for FTD/TPI versus regorafenib as second- or third-line therapy (rwORR 54.8% vs. 25.9%; adjusted OR = 4.1; all p value <.05; rwDCR 69.0% vs. 37.0%; adjusted OR = 4.9; all p value <.05). A greater proportion of patients treated with FTD/TPI versus regorafenib survived at 3 months (86.2% vs. 73.4%; p  value = .016) and 4 months (79.6% vs. 65.8%; p  value = .017). Adjusted OS hazard ratio for FTD/TPI versus regorafenib was 0.80, p  value = .157. Conclusion: Patients treated with FTD/TPI had better tumor response and disease control than patients treated with regorafenib. Subgroup analysis in second- or third-line suggests that early use of FTD/TPI may have clinical benefits. Implications for Practice: In this retrospective cohort study, patients with refractory metastatic colorectal cancer treated with trifluridine/tipiracil (FTD/TPI) were significantly less likely than those treated with regorafenib to have dose modifications and more likely to have higher real-world objective response rate (rwORR) and real-world disease control rate (rwDCR) while treated. Patients treated with FTD/TPI versus regorafenib had significantly higher odds of having rwORR or rwDCR in adjusted analyses. Monthly survival rates were higher overall in patients treated with FTD/TPI versus regorafenib in the first 6 months of follow-up, particularly at months 3 and 4. This study offers insight into patients' treatment experience in real-world clinical settings. Abstract : Real-world evidence of clinical outcomes for patients treated with regorafenib and trifluridine/tipiracil (FTD/TPI) is lacking. This article evaluates FTD/TPI versus regorafenib on clinical outcomes among patients with metastatic colorectal cancer who had progressed on or were intolerant to previous lines of therapies.